AB0244 THE IMPORTANCE OF TREATMENT STRATEGY FOR THE OUTCOME OF EARLY RHEUMATOID ARTHRITIS PATIENTS NOT RESPONDERS TO THE FIRST LINE THERAPY WITH METHOTREXATE. (June 2019) - Fedele, Anna Laura; Bruno, Dario; Tolusso, Barbara; Petricca, Luca; Ferraccioli, Gianfranco; Gremese, Elisa
Abstract : Background: According to EULAR recommendations for the management of Rheumatoid Arthritis (RA), if the treatment target is not reached with the first conventional synthetic (cs)-disease modifying antirheumatic drugs (DMARDs), addition of another csDMARD or of a biological (b)-DMARD should be considered [1]. Objectives: To evaluate the clinical and radiological outcome under combination therapy of either cs-DMARDs or b-DMARDs in our cohort of early rheumatoid arthritis (ERA) patients treated according to the treat-to-target (T2T) strategy. Methods: A total of 384 ERA patients with less than 12 months of disease duration (mean age 54.6±14.6 years, 75% female, 73.3% seropositive) were enrolled in the study. ERA patients fulfilled the 2010 ACR criteria for RA and were followed according to the T2T strategy. At baseline, and every three months, the ACR/EULAR core data set variables were recorded. At baseline and every year, hand and foot radiographs were examined according to modified Total Sharp score (mTSS). At each visit, clinical improvement and remission were evaluated according to EULAR criteria. The achievement of Comprehensive Disease Control (CDC) (28-joint Disease Activity Score using C reactive protein <2.6, Health Assessment Questionnaire <0.5 and change from baseline in mTSS ≤0.5) was assessed every year of follow-up (FU). The mean FU duration was 45.5±40.6 months. In patients not reaching the target with methotrexate (MTX) after the 3 rd -6 th month of FU, the addition of another csDMARD (chloroquine, leflunomide or sulfasalazine) or a bDMARD was considered in order to attain at least a good EULAR response. Results: At the twelfth month of FU, out of the 174 ERA patients (45.3%) not reaching the target with MTX, 97 (25.3%) were in combination therapy with csDMARDs and 77 (20.1%) were treated with csDMARDs in association with bDMARDs. Similar percentages of good EULAR response, DAS remission and CDC were registered in the two groups of patients, both at 12 th month of FU and at the last FU. Although not statistically significant, fewer bDMARD treated patients showed 5-year radiographic progression (RP) (21.7%) compared to subjects in csDMARD combination (36.8%, p=0.13). A higher BMI was observed in ERA patients who started bDMARDs (26.0±4.1) compared to subjects in combination therapy with csDMARDs (24.8±4.2, p= 0.02 ). No differences were founded regarding age and disease duration. Autoantibody positivity was comparable between the two groups. Conclusion: Our results support data suggesting that the treatment strategy is more important than the therapy used to achieve remission. In fact, when a strict protocol of tight control is applied, similar clinical and radiological outcome is achieved both in patients treated with csDMARD combination, and in subjects in bDMARD association, regardless of RA prognostic factors. A higher BMI is associated with a major frequency of bDMARD therapy, underlying a possible more csDMARD refractory disease. References: [1] Smolen JSet al, Ann Rheum Dis2017; 76:960-977 Disclosure of Interests: Anna Laura Fedele: None declared, Dario Bruno: None declared, Barbara Tolusso: None declared, Luca Petricca: None declared, Gianfranco Ferraccioli Speakers bureau: BMS, Roche, Elisa Gremese Consultant for: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Sanofi, UCB, Roche, and Pfizer, Speakers bureau: BMS, Speakers bureau: Roche, Speakers bureau: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Sanofi, UCB, Roche, and Pfizer